DYNAMICS OF DEMOCRACY: CHALLENGES AND OPPORTUNITIES IN THE DIGITAL ERA - Zainul Djumadin (Jurnal Ekonomi, 2023)
The development of information and communication technology has changed the political landscape significantly, introducing new elements that influence the democratization process. This research aims to explore and analyze the dynamics of democracy in facing the challenges and opportunities that arise in the digital era. This research uses a qualitative approach with descriptive methods. The research results show that in the digital era, people can quickly access political information, but at the same time face the risk of spreading false information and polarizing opinions. Active participation through online participatory platforms offers opportunities for citizens to be involved in decision-making processes, but unequal access to technology remains a barrier. Social media, while opening the door to wider participation, also contributes to the formation of echo chambers that can deepen gaps in views